If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3u + -24 = 3(u + -2) Reorder the terms: -24 + -3u = 3(u + -2) Reorder the terms: -24 + -3u = 3(-2 + u) -24 + -3u = (-2 * 3 + u * 3) -24 + -3u = (-6 + 3u) Solving -24 + -3u = -6 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. -24 + -3u + -3u = -6 + 3u + -3u Combine like terms: -3u + -3u = -6u -24 + -6u = -6 + 3u + -3u Combine like terms: 3u + -3u = 0 -24 + -6u = -6 + 0 -24 + -6u = -6 Add '24' to each side of the equation. -24 + 24 + -6u = -6 + 24 Combine like terms: -24 + 24 = 0 0 + -6u = -6 + 24 -6u = -6 + 24 Combine like terms: -6 + 24 = 18 -6u = 18 Divide each side by '-6'. u = -3 Simplifying u = -3
| 5x^3+x^2-6x+4=-3 | | 2.59+8p= | | 2*20-(3*7)= | | 2(w-7)=-4w+40 | | 1/3x+14=26 | | y+8=-2(x-6) | | -4w+16=-9(w+1) | | 5(x+2)-2=x+28 | | 9x^2+9x=-2 | | 90*x=3600 | | 4+21/x=0 | | 10x+30=4x+6 | | 8(x+2)-5=5x+17 | | 90x*x=3600 | | 3(x-5)+18=2x-6 | | 1.24+5p=.26 | | 50x+20.5=60 | | 9x+54=4x+19 | | 2(x-2)-8=-4 | | 7(x-5)+30=16 | | z=1.4x+168y+100 | | 5(X+3)-4x=28 | | b/20=-18 | | Y=60+.50x | | 8(1x+6)-10+1r=3(1x+12)+5 | | Y=50x+60 | | 5x^4-30x^3-x^2+6x=0 | | -5r=75 | | x-18=-1 | | 16m^2-8m=0 | | 7+16+x=39 | | 16m^2-8=0 |